2017
DOI: 10.1038/s41598-017-02828-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the clinical characteristics and brain gray matter volume alterations in unmedicated patients with major depressive disorder

Abstract: This study was to explore the sex differences in clinical characteristics and brain gray matter volume (GMV) alterations in 29 male patients with major depressive disorder (MDDm), 53 female patients with MDD (MDDf), and in 29 male and 53 female matched healthy controls. Maps of GMV were constructed using magnetic resonance imaging data and compared between groups. We evaluated clinical symptoms using the Hamilton Rating Scale for Depression and obtained a total score and five syndrome scores. A two-factor ANCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…We found stronger associations between brain-tissue based methylation levels and latelife MDD in men than in women. This finding is in line with previous studies showing sexspecific differences in serum biomarkers, mRNA expression, and brain activity of MDD cases, demonstrating that sex plays an important role in the molecular heterogeneity of MDD [41][42][43] .…”
Section: Discussionsupporting
confidence: 92%
“…We found stronger associations between brain-tissue based methylation levels and latelife MDD in men than in women. This finding is in line with previous studies showing sexspecific differences in serum biomarkers, mRNA expression, and brain activity of MDD cases, demonstrating that sex plays an important role in the molecular heterogeneity of MDD [41][42][43] .…”
Section: Discussionsupporting
confidence: 92%
“…Gender differences in depression have been widely reported in prior studies with twice the number of women diagnosed with depression than men ( Seedat et al., 2009 ). Interestingly, previous findings have also shown that women with depression suffered more sleep disturbance ( Yang et al., 2017 ). Association between clinical symptoms and severity of pneumonia is not entirely surprising, as it is commonly believed that poor physical situation are usually associated with psychological problems and worse outcomes ( Henderson & Moran, 1983 ).…”
Section: Discussionmentioning
confidence: 90%
“…Although there have been some early reports of a sex‐by‐group interaction in hippocampal volumes (e.g., Frodl et al, ), the recent large‐scale ENIGMA MDD study reported no sex‐by‐group interactions in any subcortical volumes (Schmaal et al, ). Another recent study identified sex‐by‐group interactions using VBM, including higher GMD in the left cerebellum of male patients only, and lower GMD in the dorsal medial prefrontal gyrus in female patients only (Yang et al, ). However, the sample size was relatively small (less than 100 in the patient and control group each) which may affect the reproducibility of these findings.…”
Section: Discussionmentioning
confidence: 99%